GAGALNYA KOMUNIKASI POLITIK: STUDI SEMIOTIKA ROLAND BARTHES PADA IKLAN POLITIK ANDRE ROSIADE - Sepri Yunarman (UNIVED PRESS, Universitas Dehasen Bengkulu, 2015)
This research aimed to describes the failure process of Andre Rosiade to be a Mayor candidate of Padang in 2013 from the perspective of political sociology, particularly political communication. This study found that Andre Rosiade started his socialization by using massive political advertising media. This effort was quite successful in raising the level of popularity and electability. However, in political communication only done (depending) with one political party, he failed. Roland Barthes called this phenomenon with the concept of the death of the author (The Death of the Author). This study was a qualitative research. Interviews, observation and literature study were data collection tools. The collected data were analyzed by the method negativa semiotics of Roland Barthes. The results showed that political communication built intensely by Andre through the media was not enough to convince the Party of Social Justice (PKS) to carry him become a Mayor. For Andre, political communication which he did deemed always to have denotative meaning, but it was considered to have connotative meanings for the political party.